Fifty years of African economic history. Issue 1 (2nd January 2019) - Hopkins, A. G.
ABSTRACT: The article summarizes the evolution of the study of African economic history during the past half century. It does so, not by attempting to assess the mountain of evidence that is now available, but by identifying the intellectual impulses that have shaped the contours of the subject. Six main phases have influenced several generations of postgraduate students who have been drawn to the study of Africa: modernization theory, the dependency thesis, Marxism, the Annales school, postmodernism, and, most recently, the new economic history. The discussion identifies the common features of these schools as well as their differences. Entrants to the subject, it is argued, should take encouragement from past achievements, which have opened frontiers of knowledge and set standards, but they should also be aware that the latest is not necessarily the best, nor is it always as novel as its advocates commonly suppose. Familiarity with historiographical trends enables newcomers to relate their own work to that of their predecessors. In this way, they can find room to express their own individuality and ensure that their creativity carries the subject forward.